Partisipasi Masyarakat Lokal dalam Pengembangan Pariwisata Budaya di Kampung Batik Laweyan Solo - Dewi Amelia Lestari; Arie Restama; Johny Subarkah; Ersyafaat Huda (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
This study examines community participation in the development of cultural tourism in Kampung Batik Laweyan, Solo, as well as the factors that support and hinder such involvement. This study uses a descriptive qualitative approach with observation, in-depth interviews, and documentation methods. The informants in this study include batik business actors, local community administrators, community leaders, government representatives, and non-governmental organizations (NGOs) active in the field of cultural preservation and tourism. The results of the study show that community participation is divided into three main dimensions, namely economic, socio-cultural, and institutional. In the economic aspect, the community is involved through batik businesses, homestays, and tourism services. In the socio-cultural aspect, involvement can be seen from the preservation of local traditions and the implementation of cultural activities. Meanwhile, in the institutional aspect, participation can be seen from the active role of residents in decision-making forums related to tourism management. Factors driving participation include collective awareness of the importance of cultural preservation, the economic potential of the tourism sector, and support from the government, NGOs, and educational institutions. However, community participation still faces several obstacles such as lack of education on the concept of sustainable tourism, limited access to capital, and lack of coordination between interested institutions. Cross-sectoral collaboration efforts are needed between the community, government, the private sector, and educational institutions in realizing inclusive and sustainable cultural tourism management. Thus, Laweyan Batik Village can become a model for the development of cultural tourism destinations based on active community participation. The implications of these findings suggest that cultural tourism development policies should not only focus on increasing the number of tourist visits, but also on strengthening the capacity of local communities as key actors.